Proteomic Analysis of Primary Colon Cancer and Synchronous Solitary Liver Metastasis - KIM, EUN-KYUNG (Cancer Genomics Proteomics, 2019)
Background/Aim: Colon cancer is prone to distant metastases to other sites and the risk of recurrence is relatively high. Therefore, the identification of liver metastasis-related factors is important for the diagnosis or treatment of colon cancer. The aim of this study was to identify the metastasis-related factors that are differentially expressed in synchronous solitary liver metastasis compared to primary colon cancer. Materials and Methods: Tissues of primary colon cancer and associated with liver metastases of five patients were used for mass spectrometry. Identified proteins were validated by western blotting. The in silico analysis was performed using the STRING database and GeneMANIA. Results: We identified 58 differentially expressed proteins (DEPs), including 51 under-expressed and 7 over-expressed proteins among a total of 164 identified proteins. Major hubs of protein-protein networks were ACTC1, PRDX6, TPI1, and ALDH1A1. DEPs were located in the extracellular region and cytoplasm and were involved in the regulation of enzymatic activity. The metabolic process was significantly enriched in biological processes and an involvement in the KEGG pathway. Conclusion: These DEPs can potentially be used as biomarkers for the diagnosis of liver metastasis and they may provide a new strategy for developing anti-metastatic liver drugs in colon cancer patients.